Public Librarian Perceptions of Assisting Immigrant Patrons: Results from a Multi-State Survey. - Grossman, Suzanne; Cannuscio, Carolyn C.; Feuerstein-Simon, Rachel; Winston, Mark; Agosto, Denise E.; Epstein, Nancy E.; Martinez-Donate, Ana P.; Klassen, Ann C. (Journal of Community Health, 2023)
Public libraries in the United States (U.S.) are important sources of health information. Immigrants comprise a large portion of the U.S. population, and research suggests that public libraries help immigrants adjust to life in a new country. Public libraries help immigrants access information directly related to health and provide programs that have indirect impacts on health outcomes, including learning a new language and forging social ties. The purpose of this paper was to examine perspectives from librarians related to interactions with immigrant patrons and how their library supports them in this role. Public librarians (n = 205) from two selected U.S. states completed an online survey focusing on how comfortable they were in helping immigrants with inquiries related to health and the role of the public library in supporting librarians in this endeavor. Respondents generally reported high levels of comfort interacting with immigrants, although there was limited interaction on potentially sensitive topics (i.e., immigration, health). Library staff perceived that libraries overall were not effective in meeting the needs of immigrant populations and that librarians were infrequently offered professional training related to cultural competency and diversity. The findings echo previous studies that demonstrate the need for professional development to ensure that librarians are aware of library resources available to assist immigrant patrons. Findings from this study suggest opportunities for public health professionals and public librarians to collaborate to ensure the provision of reliable resources, health information, and referrals to community-based services.